2011
DOI: 10.1364/ol.36.001008
|View full text |Cite
|
Sign up to set email alerts
|

Photonic ultrawideband signal generator using an optically injected chaotic semiconductor laser

Abstract: We propose and demonstrate a method to generate ultrawideband (UWB) signals in the optical domain based on the chaotic dynamics of an optically injected semiconductor laser with optical feedback. The chaotic-UWB pulses with a fractional bandwidth of 116% and central frequency of 6.88 GHz are experimentally generated by controlling the injection strength and frequency detuning of the chaotic laser. The spectrum of the UWB signals is in full compliance with the Federal Communications Commission spectral mask, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…For instance, high spectral purity microwave signals can be generated without a reference microwave signal by means of opto-electronic oscillators (OEO) [5,6]. Besides, other signals such as ultrawideband (UWB) can be achieved by means of more flexible schemes including MWP arbitrary waveform generators [7,8]. More specifically, one of these interesting signals is the chirped microwave pulse with the main characteristic of having a frequency variation along the time duration pulse, which involves a large bandwidth signal processing.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, high spectral purity microwave signals can be generated without a reference microwave signal by means of opto-electronic oscillators (OEO) [5,6]. Besides, other signals such as ultrawideband (UWB) can be achieved by means of more flexible schemes including MWP arbitrary waveform generators [7,8]. More specifically, one of these interesting signals is the chirped microwave pulse with the main characteristic of having a frequency variation along the time duration pulse, which involves a large bandwidth signal processing.…”
Section: Introductionmentioning
confidence: 99%
“…2012, Daniel Grodensky et al proposed and demonstrated a microwave-photonic UWB noise radar system with the waveform distributed over 10-km fiber, and a range resolution of 10cm was obtained in the experiment [5]. In previous work, photonic UWB signal generation based on nonlinear dynamics of the laser diode was proposed and demonstrated by using an optically injected semiconductor laser with optical feedback and optical feedback or optically injected semiconductor laser [6,7,8]. In this letter, in order to further improve the range resolution and scope of the radar system, combined with the previous work, we propose and demonstrate a kind of UWB microwave-photonic chaotic radar system for remote ranging.…”
Section: Introductionmentioning
confidence: 99%
“…1. The source of photonic chaotic generator in the central office unit is generated by using an optically injected semiconductor laser with optical feedback [6].…”
Section: Introductionmentioning
confidence: 99%
“…In previous works [21,22], we utilized a chaotic laser and external electroabsorption modulator to generate UWB pulse signals. However, the schemes were somewhat complex, and the generated chaotic UWB signals had a low extinction ratio.…”
Section: Introductionmentioning
confidence: 99%